Analisis Ketinggian Gelombang dan Kecepatan Angin Perairan Pesisir Bengkulu - Najwa, Farah Aulia; Johan, Henny; Defianti, Aprina; Mayub, Afrizal; Hakim, Lukmanul (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The purpose of this study is to describe wave height and wind speed in Bengkulu City over the last five years (2019–2024). This research employed a quantitative descriptive method. The data collection technique used secondary data obtained from documentation of the Meteorological, Climatological, and Geophysical Agency (BMKG) of Bengkulu Province. The data were analyzed using descriptive statistical analysis techniques. The results indicate that wave height and wind speed along the coastal waters of Bengkulu City varied significantly from January to December during the years 2019, 2020, 2021, 2022, 2023, and 2024. The months with the highest potential for high waves were June, July, August, and September, with an average wave height of 3.5–4 meters and wind speeds of 20–25 knots. The lowest and moderate waves occurred in January, February, March, April, May, October, November, and December, with wave heights ranging from 1.5–3.5 meters and wind speeds of 6–15 knots.